2020
DOI: 10.1021/acs.macromol.0c00029
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Eggs and Ladders: Understanding Exciton Landscape Formation in Aqueous π-Conjugated Inter-Polyelectrolyte Complexes

Abstract: Conjugated polymers display remarkable optoelectronic properties that emerge from the strong coupling between delocalized π-electrons, leading to highly mobile excited states. This is a very useful property from a light-harvesting perspective. We showed previously that a promising and environmentally attractive approach to formation of an ultrafast light-harvesting antenna is to use aqueous ionic assembly of oppositely charged conjugated polyelectrolytes (CPEs). However, to rationally design the excited-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…CPE–polyelectrolyte coacervation was also reported to occur in aqueous high-salt media, with the mixture’s phase behavior and photophysical properties showing a strong dependence on the identity of the cation salt . Studies on CPE–CPE complexation in salt-free water, , focusing on dilute regimes and the solid-state complexes, have further elucidated how the inclusion of the conjugated moieties fundamentally affects complexation thermodynamics. Similar to the CPE–polyelectrolyte coacervate, complexation of two CPEs in the dilute regime was shown to induce extension and planarization of the CPE backbone.…”
mentioning
confidence: 99%
“…CPE–polyelectrolyte coacervation was also reported to occur in aqueous high-salt media, with the mixture’s phase behavior and photophysical properties showing a strong dependence on the identity of the cation salt . Studies on CPE–CPE complexation in salt-free water, , focusing on dilute regimes and the solid-state complexes, have further elucidated how the inclusion of the conjugated moieties fundamentally affects complexation thermodynamics. Similar to the CPE–polyelectrolyte coacervate, complexation of two CPEs in the dilute regime was shown to induce extension and planarization of the CPE backbone.…”
mentioning
confidence: 99%
“…The color coding indicated by the circles will be used to distinguish between the salts in subsequent figures. Our choice of the CPEs was based on the following: 1) The photophysical properties of these CPEs allow them to function as an exciton donor/acceptor pair shown by their spectral overlap in Figure 1 [30] . We show in the Supporting Information that these optical properties change relatively little in different environments (Figures S14, S19, and S20).…”
Section: Resultsmentioning
confidence: 99%
“…Our prior work had shown that inter-CPE binding may be characterized by a significant thermal activation barrier. 32 Thus, we first aimed to determine whether raPTAK binding to the liposome surface was similarly temperature-dependent. We first prepared raPTAK/liposome complexes at 70% raPTAK by mole relative to DOTAP based on the total anionic raPTAK charge concentration (1 charge per monomer).…”
Section: Resultsmentioning
confidence: 99%
“…S5 † that we find excellent colocalization of raPTAK and PFPI, which was determined by separately measuring PL intensity in the polymers' distinct emission windows. 32 Two questions immediately arise: (A) do dissolved CPE chains coexist with adsorbed CPEs states? (B) Does the introduction of PFPI lead to desorption of raPTAK from the liposome surface, thereby forming dissolved PFPI/raPTAK complexes?…”
Section: Assembling An Inter-cpe Donor/acceptor Network On the Liposo...mentioning
confidence: 99%